B(E2), B(Ml) and 8(E2/ Ml) of Pt (A=198 & (Z=78) Isotope Using IBM-1 - Ibraheim, K.S; TAI-Aiawy, I; Sulaiman, H.T (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Interacting boson model version one has been used in the present theoretical calculations. The energy levels & their transitions for dynamical symmetry 0(6), SU(3), U(5), ground-state band, BetaÂ band, Gamma band, B(E2), Ot, B(Ml), ,u,gt and 6(Â£2/Ml)have been calculated to deduce the limit of Pt-198, Z=78. The present results confirmed the nuclear behavior of this isotope lay in the transitional region 0(6), SU(3) U(5). The calculations of 021 + & 022+ showed that the shape of this isotope is oblate according to Q21+ and prolate according to 022+. Most of our results are in good agreement with the available experimental results.